High-entropy metal coordination polymer and preparation method thereof
By synthesizing high-entropy metal coordination polymers by mechanochemical and chemical precipitation methods under room-low temperature conditions, the problem of difficult control of the structure of high-entropy materials is solved, and the high dispersion, controllability and wide application of the materials are achieved.
Patent Information
- Application Number
- CN202411661561.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-07
AI Technical Summary
The general adaptation and stability of existing high-entropy materials is still very difficult. Traditional preparation methods require high temperature conditions, making it difficult to accurately control the structure.
Using simple mechanochemical and chemical precipitation methods, high entropy metal coordination polymers from units to five-membered units were synthesized under room-low temperature conditions, and the material preparation was achieved through ball milling and autoclave reaction.
Highly dispersed active sites, high capacitance, controllable chemical structure and universal high entropy metal coordination polymers are achieved. They can be used as fixing agents and catalysts for polysulfides and are widely used in supercapacitors, sensors, electrocatalysis and other fields.
Smart Images

Figure CN119569082A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high entropy metal coordination polymers, and in particular to a high entropy metal coordination polymer and a preparation method thereof. Background Art
[0002] In recent years, the application of traditional low-entropy nanomaterials has been limited by their poor densification and low fracture toughness, while high-entropy materials provide a huge platform for the modification and performance regulation of new materials due to their nearly infinite arrangement and combination of multiple components. Multiple main elements will also produce new properties while balancing the performance. However, the universal synthesis and stability of high-entropy materials, especially high-entropy compounds, are still very difficult. Traditional preparation methods have strict requirements on experimental conditions, such as high temperature is required to overcome the reaction energy barrier, making it difficult to accurately control the structure of high-entropy materials. Therefore, the development of a low-temperature or room-temperature method to accurately prepare high-entropy compound materials with controllable structure and composition and universality is the primary problem facing this field. Summary of the invention
[0003] The purpose of the present invention is to provide a high entropy metal coordination polymer and a preparation method thereof in view of the above-mentioned deficiencies of the prior art. The preparation method synthesizes high entropy metal coordination polymers from single to five members by simple mechanochemistry and chemical precipitation methods, and the material has the advantages of highly dispersed active sites, high capacitance, controllable chemical structure and universality.
[0004] A method for preparing a high entropy metal coordination polymer of the present invention comprises the following steps:
[0005] S1, stirring the ball-milled metal salt with an aqueous solution of potassium ferrocyanide and drying the mixture to obtain a metal coordination polymer;
[0006] S2. The metal coordination polymer is mixed with solid sulfur powder, ball-milled, and reacted in a Teflon autoclave to obtain a high entropy metal coordination polymer.
[0007] Furthermore, the metal salt is one or more of Mn salt, Co salt, Ni salt, Cu salt and Fe salt.
[0008] Furthermore, the anion of the metal salt includes one or more of nitrate ion, sulfate ion, acetate ion or chloride ion.
[0009] Furthermore, the metal salt is one or more of manganese nitrate, cobalt chloride, nickel acetate tetrahydrate, copper nitrate and ferrous sulfate.
[0010] Furthermore, when there are multiple metal salts, the molar ratio between every two metal salts is 1-3:1-3.
[0011] Furthermore, the molar ratio of the metal salt to potassium ferrocyanide is 1-2:1.
[0012] Furthermore, the mass ratio of the metal coordination polymer to the solid sulfur powder is 4-5:10.
[0013] Furthermore, in step S1, the stirring time is 10-15 minutes, the drying temperature is 80-100° C., and the drying time is 20-24 hours.
[0014] Furthermore, in step S2, the reaction temperature is 120-140° C. and the reaction time is 10-15 hours.
[0015] A high entropy metal coordination polymer prepared by the above preparation method.
[0016] The present invention is based on five metal cations (Mn 2+ 、Co 2+ 、Ni 2+ , Cu 2+ and Fe 2+ ) synthesized high-entropy metal coordination polymers with controllable structures and compositions from single to five members at room-temperature (normal temperature -130°C) by simple mechanochemical and chemical precipitation methods.
[0017] The high-entropy metal coordination polymer prepared by the present invention can not only be used as a fixative for polysulfides to inhibit the shuttling effect of polysulfides, which is mainly manifested in three aspects, namely, preventing the generation of long-chain polysulfides, preventing the separation of polysulfides from sulfur host structures, and reducing the solubility of polysulfides; it can also be used as a catalyst to promote the conversion of polysulfides to achieve charge transfer and storage, which is mainly manifested in two aspects, namely, the constructed three-dimensional conductive network can anchor polysulfides and enhance charge transfer, and the formed active sites can accelerate the conversion of polysulfides and form a carbon coating layer to improve the stability of charge storage.
[0018] The high entropy metal coordination polymer prepared by the present invention can not only serve as a polysulfide fixative by enhancing the inhibitory effect on the polysulfide shuttle effect, but also can serve as a catalyst to promote the conversion of polysulfides to achieve charge transfer and storage, so that it can be used to prepare supercapacitors and can be widely used in clean energy, intelligent response materials, high-performance device preparation, supercapacitors and other fields.
[0019] The high-entropy metal coordination polymer prepared by the present invention has the advantages of controllable chemical structure, stable performance, simple synthesis procedure, low price and non-toxic raw materials, which promotes its wide application in the fields of sensors, electrocatalysis, photocatalysis, gas storage and sodium ion batteries. This breakthrough is expected to have a significant market impact in a short period of time. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1The binary, ternary, quaternary and multi-element metal coordination polymer mixed solution samples prepared in Examples 2-5;
[0021] Figure 2 The SEM images of binary metal coordination polymers, ternary metal coordination polymers, quaternary metal coordination polymers and the TEM images of multi-metal coordination polymers;
[0022] Figure 3 This is a SEM image of the high entropy metal coordination polymer prepared in part 2 of Example 5;
[0023] Figure 4 XRD patterns of multi-metal coordination polymers and high entropy metal coordination polymers;
[0024] Figure 5 A schematic diagram of the equivalent circuit. DETAILED DESCRIPTION
[0025] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.
[0026] Example 1
[0027] 1. Preparation of single metal coordination polymers
[0028] 1) In an air environment, a mixture of 2.5 mmol potassium ferrocyanide (K3[Fe(CN)6]) and 2.5 mmol manganese nitrate (Mn(NO3)2) was placed in a ball mill and ball-milled at a speed of 20 Hz for 120 minutes to obtain a solid powder a;
[0029] 2) Dissolve the solid powder a in 100 mL of deionized water, stir for 5-10 minutes and filter to obtain a solid precipitate, dry it in a 100°C environment for 24 hours to obtain a Mn-metal coordination polymer; the synthesis method of other single metal (Co, Ni, Cu, Zn) coordination polymers is the same as above to obtain M1-metal coordination polymers (where M1 represents Mn, Co, Ni, Cu, Fe ions).
[0030] 2. Preparation of high entropy metal coordination polymers
[0031] In an air environment, 43 mg of M1-metal coordination polymer solid powder and 100 mg of nano-scale solid sulfur powder were respectively put into a ball mill and ball-milled at a speed of 20 Hz for 120 minutes to obtain solid powder g1;
[0032] In an air environment, the solid powder g1 was placed in a 50 mL Teflon autoclave and heated at 130° C. for 12 hours to obtain a high entropy metal coordination polymer, namely HM1-metal coordination polymer.
[0033] Example 2
[0034] 1. Preparation of binary metal coordination polymers
[0035] 1) In an air environment, a mixture of 2 mmol copper nitrate (Cu(NO3)2) and 2 mmol manganese nitrate (Mn(NO3)2) was placed in a ball mill and ball-milled at a speed of 20 Hz for 120 minutes to obtain a solid powder b;
[0036] 2) In an air environment, dissolve 2 mmol of potassium ferrocyanide (K3[Fe(CN)6]) in 50 mL of deionized water to obtain solution c;
[0037] 3) In an air environment, place the solid powder b into the solution c, stir continuously for 10-15 minutes, and then dry it in a 100°C environment for 24 hours to obtain a binary CuMn-metal coordination polymer; the synthesis method of other binary metal (CoFe, NiFe, CuFe, MnFe, etc.) coordination polymers is as above to obtain M2-metal coordination polymers (where M2 represents any two of Mn, Co, Ni, Cu, and Fe ions).
[0038] 2. Preparation of high entropy metal coordination polymers
[0039] In an air environment, 43 mg of M2-metal coordination polymer solid powder and 100 mg of solid sulfur powder ball-milled to nanometer level were respectively put into a ball mill and ball-milled at a speed of 20 Hz for 120 minutes to obtain solid powder g2;
[0040] In an air environment, the solid powder g2 was placed in a 50 mL Teflon autoclave and heated at 130° C. for 12 hours to obtain a high entropy metal coordination polymer, namely HM2-metal coordination polymer.
[0041] Example 3
[0042] 1. Preparation of ternary metal coordination polymers
[0043] 1) In an air environment, a mixture of 1.5 mmol copper nitrate (Cu(NO3)2), 1.5 mmol manganese nitrate (Mn(NO3)2) and 0.5 mmol ferrous sulfate (FeSO4) was placed in a ball mill and ball-milled at a speed of 20 Hz for 120 minutes to obtain a solid powder d;
[0044] 2) In an air environment, dissolve 2 mmol of potassium ferrocyanide (K3[Fe(CN)6]) in 50 mL of deionized water to obtain solution c;
[0045] 3) In an air environment, place the solid powder d into the solution c, stir continuously for 10-15 minutes, and then dry it in a 100°C environment for 24 hours to obtain a ternary CuMnFe-metal coordination polymer; the synthesis method of other ternary metal (CoNiFe, NiCuFe, CuZnFe, NiZnFe, CoMnFe, NiMnFe, etc.) coordination polymers is as above to obtain M3-metal coordination polymers (where M3 represents any three of Mn, Co, Ni, Cu, and Fe ions).
[0046] 2. Preparation of high entropy metal coordination polymers
[0047] In an air environment, 43 mg of M3-metal coordination polymer solid powder and 100 mg of solid sulfur powder ball-milled to nanometer level were respectively put into a ball mill and ball-milled at a speed of 20 Hz for 120 minutes to obtain solid powder g3;
[0048] In an air environment, the solid powder g3 was placed in a 50 mL Teflon autoclave and heated at 130° C. for 12 hours to obtain a high entropy metal coordination polymer, namely HM3-metal coordination polymer.
[0049] Example 4
[0050] 1. Preparation of quaternary metal coordination polymers
[0051] 1) In an air environment, a mixture of 1.5 mmol copper nitrate (Cu(NO3)2), 1.5 mmol manganese nitrate (Mn(NO3)2), 0.5 mmol ferrous sulfate (FeSO4) and 0.5 mmol nickel acetate tetrahydrate (Ni(CH3COO)2·4H2O) was placed in a ball mill and ball-milled at a speed of 20 Hz for 120 minutes to obtain a solid powder e;
[0052] 2) In an air environment, dissolve 2 mmol of potassium ferrocyanide (K3[Fe(CN)6]) in 50 mL of deionized water to obtain solution c;
[0053] 3) In an air environment, place the solid powder e into the solution c, stir continuously for 10-15 minutes, and then place it in a 100°C environment to dry for 24 hours to obtain a quaternary NiCuMnFe-metal coordination polymer; the synthesis method of other quaternary metal (CoNiCuFe, NiCuZnFe, CoNiMnFe, etc.) coordination polymers is as above to obtain M4-metal coordination polymers (where M4 represents any 4 of Mn, Co, Ni, Cu, and Fe ions).
[0054] 2. Preparation of high entropy metal coordination polymers
[0055] In an air environment, 43 mg of M4-metal coordination polymer solid powder and 100 mg of solid sulfur powder ball-milled to nanometer level were respectively put into a ball mill and ball-milled at a speed of 20 Hz for 120 minutes to obtain solid powder g4;
[0056] In an air environment, the solid powder g4 was placed in a 50 mL Teflon autoclave and heated at 130° C. for 12 hours to obtain a high entropy metal coordination polymer, namely HM4-metal coordination polymer.
[0057] Example 5
[0058] 1. Preparation of multi-metal coordination polymers
[0059] 1) In an air environment, a mixture of 0.4 mmol copper nitrate (Cu(NO3)2), 0.4 mmol manganese nitrate (Mn(NO3)2), 0.4 mmol ferrous sulfate (FeSO4), 0.4 mmol nickel acetate tetrahydrate (Ni(CH3COO)2·4H2O) and 0.4 mmol cobalt chloride (CoCl2) was placed in a ball mill and ball-milled at a speed of 20 Hz for 120 minutes to obtain a solid powder f;
[0060] 2) In an air environment, dissolve 2 mmol of potassium ferrocyanide (K3[Fe(CN)6]) in 50 mL of deionized water to obtain solution c;
[0061] 3) In an air environment, solid powder f is placed in solution c, and after continuous stirring for 10-15 minutes, it is placed in a 100°C environment and dried for 24 hours to obtain a multi-component NiCuMnFe-metal coordination polymer, i.e., M5-metal coordination polymer (where M5 represents NiCuMnCoFe ions).
[0062] 2. Preparation of high entropy metal coordination polymers
[0063] In an air environment, 43 mg of M5-metal coordination polymer solid powder and 100 mg of solid sulfur powder ball-milled to nanometer level were respectively put into a ball mill and ball-milled at a speed of 20 Hz for 120 minutes to obtain solid powder g5;
[0064] In an air environment, the solid powder g5 was placed in a 50 mL Teflon autoclave and heated at 130° C. for 12 hours to obtain a high entropy metal coordination polymer, namely HM5-metal coordination polymer.
[0065] Figure 1 These are the binary, ternary, quaternary and multi-component metal coordination polymer mixed solution samples prepared in Examples 2-5.
[0066] Figure 2These are SEM images of binary metal coordination polymers, ternary metal coordination polymers, quaternary metal coordination polymers, and multi-metal coordination polymers; among them, Figure a is the SEM image of the binary metal coordination polymer; Figure b is the SEM image of the ternary metal coordination polymer; Figure c is the SEM image of the quaternary metal coordination polymer; Figure d is the TEM image of the multi-metal coordination polymer.
[0067] As can be seen from Figure a, the binary metal coordination polymer has a regular hexagonal structure with uniform pore distribution. This structure helps to increase the surface area of the material, thereby enhancing its gas adsorption capacity; as can be seen from Figure b, the structure of the ternary metal coordination polymer shows more complex polygonal pores with neat edges, and the ternary metal ions may enhance the stability and functionality of the structure; as can be seen from Figure c, the quaternary metal coordination polymer has a honeycomb-like structure, and the pores are larger and more open than the previous two. This open structure is conducive to the entry and exit of large molecules, making it exhibit good performance in catalysis and molecular screening; as can be seen from Figure d, the nanoscale pore structure inside the multi-metal coordination polymer shows a complex multi-level organization. The resolution of this image is high, and the interconnection between the pores can be clearly seen, which is crucial for studying the diffusion properties of the material. In general, Figure 2 The structural differences of different metal coordination polymers at the microscopic level are revealed, which directly affect their physical and chemical properties.
[0068] Figure 3 This is a SEM image of the high entropy metal coordination polymer prepared in part 2 of Example 5; Figure 3 It can be seen that each unit exhibits clear edges and vertices, which indicates that the crystal growth of the material is well controlled during the synthesis process. This regular shape helps to achieve higher structural regularity and possible pore uniformity; the granular characteristics of the surface characterize the non-ideal reaction kinetics during the growth of the material, resulting in local structures of various morphologies. The existence of these surface structures can provide more active sites; some of the structures shown in the figure are in contact with each other, which may indicate that aggregation occurred during the synthesis process, and this aggregation may affect the pore distribution and overall stability of the material.
[0069] Figure 4 The XRD graphs of multi-metal coordination polymers and high entropy metal coordination polymers are shown in Figure 1. Multi-metal coordination polymers (without sulfur): The red spectrum shows sharp and well-defined diffraction peaks, which indicates that the material has high crystallinity. Sharp peaks usually indicate that the material has good order inside and the atoms are neatly arranged; the diffraction peaks are mainly concentrated in the lower 2θ angle region, indicating that the lattice parameter of the material is large and the pores may be wide.
[0070] High-entropy metal coordination polymer (after sulfur addition): The diffraction peaks of the blue spectrum are stronger, sharper and narrower than those of the unsulfurized sample, which is usually a sign of improved crystal quality. This indicates that the sulfurization process may promote further nucleation and growth of crystals, thereby improving the crystallinity of the material. The position of the diffraction peaks does not change much, indicating that the sulfurization treatment may not significantly change the crystal structure of the material, but may enhance the order and integrity of the lattice.
[0071] Relationship between crystallinity and application: Enhanced crystallinity usually helps to improve the mechanical and chemical stability of the material, which is particularly important for the material in adsorption, storage and catalytic applications. For example, sulfur addition introduces additional cross-linking points or functional groups into the pore structure of the material, which helps to enhance the adsorption capacity or selectivity of specific molecules.
[0072] In summary, by comparing the XRD patterns of unsulfurized and sulfurized samples, it can be found that sulfur treatment may help to improve the crystallinity and functionality of the material.
[0073] use Figure 5 The device shown was used to test the performance of the high entropy metal coordination polymers prepared in Examples 1-5. The equivalent circuit and fitted electrochemical kinetic parameters are shown in Table 1.
[0074] Table 1
[0075] sample Rs(Ω) Rct(Ω) HM1-Metal Coordination Polymer 2.80 38.79 HM2-Metal Coordination Polymer 3.89 43.55 HM3-Metal Coordination Polymer 4.15 91.28 HM4-Metal Coordination Polymer 4.24 23.68 HM5-Metal Coordination Polymer 3.88 22.35
[0076] Regression analysis was performed on Table 1 to explore the effect of solution resistance on charge transfer resistance, that is, Rs (solution resistance) was used as the independent variable x, and Rct (charge transfer resistance) was used as the dependent variable y. The resulting linear regression equation was:
[0077] R ct =12.45+8.30·R s .
[0078] It shows that there is a certain positive correlation between Rs and Rct. The change of solution resistance Rs affects the charge transfer resistance Rct by changing the interface potential difference or affecting the kinetics of the electrode process. The fitting results provide quantitative support for the conductivity and kinetic behavior of metal coordination polymers.
[0079] For matters not mentioned above, the prior art applies.
[0080] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high entropy metal coordination polymer, characterized in that: The steps include: S1, stirring the ball-milled metal salt with an aqueous solution of potassium ferrocyanide and drying the mixture to obtain a metal coordination polymer; S2. The metal coordination polymer is mixed with solid sulfur powder, ball-milled, and reacted in a Teflon autoclave to obtain a high entropy metal coordination polymer.
2. The preparation method according to claim 1, characterized in that: The metal salt is one or more of Mn salt, Co salt, Ni salt, Cu salt and Fe salt.
3. The preparation method according to claim 2, characterized in that: The anion of the metal salt includes one or more of nitrate ion, sulfate ion, acetate ion or chloride ion.
4. The preparation method according to claim 1, characterized in that: The metal salt is one or more of manganese nitrate, cobalt chloride, nickel acetate tetrahydrate, copper nitrate and ferrous sulfate.
5. The preparation method according to claim 1, characterized in that: When there are multiple metal salts, the molar ratio between every two metal salts is 1-3:1-3.
6. The preparation method according to claim 1, characterized in that: The molar ratio of the metal salt to potassium ferrocyanide is 1-2:
1.
7. The preparation method according to claim 1, characterized in that: The mass ratio of the metal coordination polymer to the solid sulfur powder is 4-5:
10.
8. The preparation method according to claim 1, characterized in that: In step S1, the stirring time is 10-15 minutes, the drying temperature is 80-100° C., and the drying time is 20-24 hours.
9. The preparation method according to claim 1, characterized in that: In step S2, the reaction temperature is 120-140° C. and the reaction time is 10-15 hours.
10. A high entropy metal coordination polymer prepared by the preparation method according to any one of claims 1 to 9.